Idiocracy - Shapiro, Theodore 1971- (Twentieth Century Fox Home Entertainment LLC, 2007)
Joe Bowers is an average Joe. He is not the sharpest tool in the shed. He becomes part of a government experiment to go into hibernation. The experiment goes awry and Bowers awakens in the year 2505 to find a society so dumbed-down by mass commercialism and mindless TV programming that he's become the smartest guy on the planet. Now it's up to this average Joe to get human evolution back on the right track
Bildformat: 16:9 widescreen version
Sonderausstattung: 5 nicht verwendete Szenen
Spielfilm. USA. 2006
Keywords: Science-Fiction-Film; Filmkomödie; Future life / Drama; Stupidity / Drama; Hibernation / Drama; Mass media / Drama; Television programs / Drama; Television / Psychological aspects / Drama; Future life; Hibernation; Mass media; Stupidity; Television programs; Television / Psychological aspects; Action and adventure films; Drama; Dystopian films; Science fiction films; Video recordings for the hearing impaired; Comedy films; Feature films; Film; DVD-Video